PENGARUH MANAJAMEN MODAL KERJA DAN RASIO KEUANGAN TERHADAP PROFITABILITAS PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2011 - Antonius Lokollo; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
This study aims to examine the influence of working capital management and financial ratiostoward profitability. Research was carried out by test the influence of average collection period (ACP), inventory turnover in days (ITID), average payment period (APP), logarithm of sales (LOS), debt ratio(DER) and current ratio (CR) toward net operating profitability (NOP).Sampling method used is purposive sampling with criteria as follows: (1) Manufacturing companies listed at Indonesia Stock Exchange (BEI) during 2011 and (2) published financial statements during 2011 completely. Based on these criteria, obtained 135 companies over  of observation. Then, there are 14 samples that included outlier should be excluded from samples of observation. So,the last amount of the final sample for observation are 121 firms. Data analysis with multilinier regression of ordinary least square and hypotheses test used partial t – test and adjusted R square. Empirical evidence shows that, partially,average collection period (ACP), inventory turnover in days (ITID), average payment period (APP), debt ratio (DER) and current ratio (CR) have negative significant influence toward profitability (NOP). logarthym of sales (LOS) have positive significant influence toward profitability (NOP). These is indicated by adjusted R ² of the model is 0,462 based on the test result of adjusted R square.